THE DEPLETION AND REGENERATION OF DISSOLUTION-ACTIVE SITES AT THE MINERAL-WATER INTERFACE: II. REGENERATION OF ACTIVE SITES ON α-FE2O3 AT PH 3 AND PH 6 - Samson S.D.; Eggleston C.M. (My University, 2000)
Periods of transient nonsteady state dissolution can contain much information about dissolution mechanisms. Here, pH-jump-induced dissolution transients are used to explore the kinetics of production, at pH 3 and pH 6, of α-Fe2O3 surface sites active for dissolution at pH 1. We find that such sites are generated in a matter of minutes or less at higher pH. The steady state dissolution rate of hematite at pH 1 is =<10.7 pmol m-2 s-1, whereas the rate of active site production at pH 6 in the first 30 min. of aging is at least 119 pmol m-2 s-1. Apparently, active sites are produced relatively slowly at low pH and relatively rapidly at circumneutral pH, despite the fact that dissolution rates are near a minimum at circumneutral pH. Using aqueous water exchange rates as a proxy for surface ligand exchange rates, this is qualitatively consistent with relatively slow water exchange by aqueous Fe3+ ions at low pH and relatively rapid water exchange by Fe3+ hydrolysis products (e.g., Fe(OH)2+) at circumneutral pH. Consequently, the highest overall dissolution rates are achieved not at steady state at low pH, but by cycling between neutral and low pH. Our results call into question the assumption that oxide mineral surfaces, particularly those of iron and aluminum oxides, are inert on the time scale of proton or ligand adsorption (e.g., during the acid-base titrations typically used to measure oxide surface charge due to proton adsorption).